Perceptions of standardized English examinations, pressure to improve scores, and effects on classroom practices among secondary school teachers in Malaysia - Zakaria, Noor Asma Iffah (2014)
This study surveys English language (n=244) teachers‟ perceptions of standardized English examinations, pressure to improve students‟ scores and how these factors have affected their classroom practices. In this study, the classroom practices are determined by four variables which are; (i) test preparation activities, (ii) mode of instruction employed in English class, (iii) content/areas covered during English lesson, and (iv) teachers‟ involvement in motivational practices. Responses were analysed by using Multivariate Analysis of Variance (MANOVA) to determine whether there are any significant differences in terms of the classroom practices and the perceptions and pressure subgroups. This study found that teachers have moderate to positive perceptions towards the examinations. However, the type of questions and coverage of content in the standardized English examinations have been taken into consideration in their classroom practices regardless of their differential perceptions towards the examinations. This study also found that there are significant differences in terms of the test preparation activities, content and motivational activities according to the teachers‟ levels of pressure to improve students‟ scores in standardized English examinations.